Lexicon of Costumes in The Rangda Dance - Pande Agus Putu Dharma Putra; I Gede Budasi; Dewa Putu Ramendra (JALL (Journal of Applied Linguistics and Literacy), 2023)
Balinese culture has many traditions. One of the traditions in Bali is the Balinese dance that exists in Bali. Several dances have a sacred meaning for Balinese people. One of the dances is the Rangda dance. This dance contains many lexicons in the dance's costumes. This study aimed to discover the lexicons that exist in Rangda dance costumes. This study is designed as descriptive qualitative research using the ecolinguistics approach. The data were obtained through observation and interviews with selected informants. The study's result shows that twenty-seven lexicons exist in Rangda dance costumes. The data were categorized into the lexicons in the mask (ten lexicons) and lexicons on the costume (seventeen lexicons). Those lexicons including tapel rangda, terang, kumba, petitis, lidah api, teteh api, jangar api, rambut, jebug, bungan jepun, jaler reringitan, baju reringitan, udeng, badong mute, badong kulit, angkeb baong, tapih, ampok ampok, kuku, basang basang, sabuk, baju pepontangan, jaler pepontangan, semayut, nyonyo. galeng, and kereb.